Clinical Value of Asymmetrical Dimethylarginine Detection in Patients with Connective Tissue Disease-Associated Pulmonary Arterial Hypertension - Juan Liu; Qiang Fu; Lili Jiang; Youlian Wang (Cardiology Research and Practice)
Objective. To evaluate the clinical value of serum asymmetrical dimethylarginine (ADMA) in patients with connective tissue disease- (CTD-) associated pulmonary arterial hypertension (PAH). Methods. 88 patients with CTD were recruited between December 2017 and August 2018 in Jiangxi Provincial People’s Hospital. Patients were further divided into two groups: CTD-without PAH (n = 45 cases) and CTD-with PAH (n = 43 cases), according to the pulmonary systolic blood pressure measured by echocardiography. 40 healthy controls were also included (n = 40 cases). The clinical data, including laboratory examinations, echocardiographic measurements, pulmonary function, and serum ADMA levels determined by enzyme-linked immunosorbent assay, (ELISA) were collected. The correlation between ADMA levels and the occurrence of PAH, pulmonary function, and other laboratory indexes in CTD patients were analyzed. Statistical analyses were performed by SPSS (version 23); P<0.05 was considered statistically significant. Results. The serum levels of ADMA in the CTD-PAH group were significantly higher than those of the CTD-without PAH group and healthy control group (P<0.05); the serum ADMA levels were (0.706 ± 0.153 μmol/L), (1.015 ± 0.122 μmol/L), and (0.661 ± 0.113 μmol/L), respectively. There was no significant difference between the CTD-without PAH group and healthy control group (P<0.05). Correlation analysis showed that serum ADMA levels were positively correlated with sPAP and NT-proBNP and negatively correlated with DLCO% (r = 0.802, 0.475, −0.585, P<0.001). Multivariate analysis indicated that elevated serum ADMA levels increased the risk for the appearance of PAH in CTD patients (OR = 57.460, P<0.001). Using the receiver operating characteristic (ROC) curve analysis, at the cutoff level of 0.810 μmol/L, ADMA showed good diagnostic efficacy as follows: sensitivity was 97.7%, specificity was 75.6%, and the area under the curve (AUC) was 0.947 (P<0.001). Conclusion. Increased ADMA levels are independently associated with the presence and severity of PAH in CTD patients. The levels of ADMA in the serum may contribute to be a noninvasive indicator for early diagnosis of CTD-with PAH patients.